2004
DOI: 10.1016/s0741-5214(03)00720-1
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic thigh arteriovenous access: outcome with SVS/AAVS reporting standards

Abstract: Prosthetic AV access in the thigh is associated with higher morbidity compared with that reported for the upper extremity, and should be considered only if no upper extremity AV access option is available. Early access failure and the requirement for an increased number of interventions to reestablish and maintain access patency are more common in patients with diabetes mellitus and obesity. The number of interventions per year of access patency is a valuable end point when assessing the outcome of AV access p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
93
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 9 publications
8
93
3
Order By: Relevance
“…Compared with arm grafts, thigh grafts had a lower thrombosis rate (1.457 versus 0.543/patient-year) and required fewer total PTAs (1.977 versus 0.881/patient-year) to maintain patency (Table 2). These rates are similar to those reported in the literature (10,11). We speculate that the larger diameter of arteries and veins in the thigh may play a role in the lower thrombosis rate observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with arm grafts, thigh grafts had a lower thrombosis rate (1.457 versus 0.543/patient-year) and required fewer total PTAs (1.977 versus 0.881/patient-year) to maintain patency (Table 2). These rates are similar to those reported in the literature (10,11). We speculate that the larger diameter of arteries and veins in the thigh may play a role in the lower thrombosis rate observed.…”
Section: Discussionsupporting
confidence: 91%
“…Because grafts are preferable to catheters, it is conceivable that thigh grafts would benefit these patients. Thus, several studies have shown that the outcome of thigh grafts is similar to concurrent or historic arm grafts (9 -12); however, there is a general reluctance to thigh graft placement because of the prevailing impression of poor performance or associated risks for infection or leg ischemia (9,11).…”
mentioning
confidence: 99%
“…We found no significant association of secondary survival, primary assisted survival, or infection-free graft survival with patient age, sex, race, diabetes, vascular disease, or heart failure. In agreement with our findings, another large series (125 grafts) found no significant association of secondary graft patency with patient age, sex, race, or diabetes, but that study did not look at vascular disease or heart failure (12). Likewise, another large series (153 grafts) observed no significant association between thigh graft infection and patient age, sex, diabetes, or coronary artery disease (14).…”
Section: Discussionsupporting
confidence: 89%
“…Most published studies reported the outcomes of relatively few thigh grafts, with inconsistent definitions of graft outcomes (3)(4)(5)(6)(7)(8)(9)(10)(11). Three larger series (.100 thigh grafts) (12)(13)(14) provided information about graft outcomes using standardized definitions (15) but did not comprehensively analyze clinical factors or comorbid conditions that are associated with thigh graft outcomes. Finally, none of the published reports directly compared the outcomes of thigh grafts and tunneled dialysis catheters.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports of survival after ePTFE graft implantation range from 53 to 96 per cent 20,21 compared with 62 per cent for biological grafts 22 . Another xenograft conduit, the ProCol  bovine mesenteric vein graft (Hancock Jaffe Laboratories, Irvine, California, USA) had patient survival rates of 77 and 86 per cent 23,24 .…”
Section: Discussionmentioning
confidence: 94%